Propuesta para obtener la certificación Fairtsa en comercio justo de la Asociación Agro - Artesanal la Pepa de Oro, Bolívar – Manabí - Sabando Vera, María Mercedes (2016)
The research aimed to develop a proposal to get a certification in cocoa Fair Trade association La Pepa de Oro, located in Bolivar-Manabi. To develop the Study there were some different techniques applied such as: field research, bibliographic research, deep interviews and surveys that allowed us to know the internal and external situation of the association in relation to social, productive, economic and environmental conditions. The population consisted of 33 producers and sampling used was non-probabilistic intentional. From situational analysis the SWOT method was applied in order to analyze and summarize the strengths and weaknesses of the organization. Other matrices were consecutively developed for the MEFE, MEFI and evaluation certification. For this procedure expert criteria used and thus evaluate the performance of the association and the criteria that have greater weight. Then the CAME analysis was performed to correct weaknesses, confront threats, maintain the potential of the association and exploit opportunities; when finished this step a strategic plan of variables that are in a critical state actions raised. In conclusion this company fulfills 56% corresponding of the basic criteria and development of social, productive, economic and environmental dimensions; therefore continuous monitoring of the requirements of Fair Trade (FAIRTSA) is needed, and; also the monitoring and control of the strategic plan to check the progress or fulfillment of each of the proposed strategies.